2009
DOI: 10.1523/jneurosci.0704-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dependence of Action Selection on Recent Motor History in Parkinson's Disease

Abstract: It is well known that the basal ganglia are involved in switching between movement sequences. Here we test the hypothesis that this contribution is an instance of a more general role of the basal ganglia in selecting actions that deviate from the context defined by the recent motor history, even when there is no sequential structure to learn or implement. We investigated the effect of striatal dopamine depletion [in Parkinson's disease (PD)] on the ability to switch between independent action plans. PD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 61 publications
5
62
2
Order By: Relevance
“…The identified areas would likewise belong to components of the salience network considered responsible for switching between activation and deactivation of large-scale brain networks so as to support different general functional states of the brain (Sridharan et al, 2008). The involvement of the putamen and the ventral striatopallidum corroborates the view that basal ganglia and frontostriatal circuits are of importance for switching between task sets rather than resolving control issues within task sets or particular movements (Cools et al, 1984;Mink, 1996;Redgrave et al, 1999;Rushworth et al, 2002;Helmich et al, 2009).…”
Section: Task Set Switchingsupporting
confidence: 57%
“…The identified areas would likewise belong to components of the salience network considered responsible for switching between activation and deactivation of large-scale brain networks so as to support different general functional states of the brain (Sridharan et al, 2008). The involvement of the putamen and the ventral striatopallidum corroborates the view that basal ganglia and frontostriatal circuits are of importance for switching between task sets rather than resolving control issues within task sets or particular movements (Cools et al, 1984;Mink, 1996;Redgrave et al, 1999;Rushworth et al, 2002;Helmich et al, 2009).…”
Section: Task Set Switchingsupporting
confidence: 57%
“…Such task-related FC is not as commonly studied as resting-state FC, though several groups have published measures of effective connectivity (EC) during a task (Helmich et al, 2009;Palmer et al, 2009Palmer et al, , 2010Wu et al, 2010Wu et al, , 2011b. EC differs from FC in that it is measured during a traditional fMRI scan (i.e., with alternating task blocks), rather than in what we refer to as an fcMRI scan, in which the subject is in a constant state throughout the entire scan.…”
Section: Discussionmentioning
confidence: 99%
“…We characterize functional and structural markers of cortical changes associated with the LRRK2 G2019S mutation, comparing asymptomatic LRRK2 carriers with non-mutation carriers. We assess a core deficit of Parkinson's disease: the internal selection of motor representations (Brown and Marsden, 1988;Helmich et al, 2009). To identify these markers, we use a validated motor imagery task in which subjects are asked to make laterality judgements (left or right) of hand pictures (de Lange et al, 2005;Helmich et al, 2009) while measuring behavioural performance (reaction times) and cerebral activity (using functional MRI).…”
Section: Introductionmentioning
confidence: 99%
“…We assess a core deficit of Parkinson's disease: the internal selection of motor representations (Brown and Marsden, 1988;Helmich et al, 2009). To identify these markers, we use a validated motor imagery task in which subjects are asked to make laterality judgements (left or right) of hand pictures (de Lange et al, 2005;Helmich et al, 2009) while measuring behavioural performance (reaction times) and cerebral activity (using functional MRI). Previous studies have shown that subjects solve this task by mentally moving their own hand from its current position into the stimulus orientation for comparison (Parsons, 1987;de Lange et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%